2019
DOI: 10.3390/min9100632
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization of Monohydrocalcite Induced by the Halophile Halomonas Smyrnensis WMS-3

Abstract: The halophilic bacterium Halomonas smyrnensis from a modern salt lake used in experiments to induce biomineralization has resulted in the precipitation of monohydrocalcite and other carbonate minerals. In this study, a Halomonas smyrnensis WMS‐3 (GenBank:MH425323) strain was identified based on 16S rDNA homology comparison, and then cultured in mediums with 3% NaCl concentration to induce monohydrocalcite at different Mg/Ca molar ratios of 0, 2, 5, 7, and 9. The growth curve of WMS‐3 bacteria, pH values, NH4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 93 publications
0
26
0
2
Order By: Relevance
“…As seen from Figure 7a Figure 7b) and these functional groups may be due to the amino acids and polysaccharides there. The FTIR spectra of supernatants, after the minerals were processed by thorough ultrasonic shaking, are identical with the distilled water ( Figure 7c) [11]; this indicates that the organic substances on the mineral surfaces were removed completely. Some organic functional groups within the mineral interiors at various Mg/Ca ratios, such as C-O-C, C-O, O-H, C-H and C=O, were also detected, shown in Figure 7d; most of these organic functional groups were also detected in the EPS from the ZW123 bacterium (Figure 7b).…”
Section: Ftir Analysesmentioning
confidence: 74%
See 2 more Smart Citations
“…As seen from Figure 7a Figure 7b) and these functional groups may be due to the amino acids and polysaccharides there. The FTIR spectra of supernatants, after the minerals were processed by thorough ultrasonic shaking, are identical with the distilled water ( Figure 7c) [11]; this indicates that the organic substances on the mineral surfaces were removed completely. Some organic functional groups within the mineral interiors at various Mg/Ca ratios, such as C-O-C, C-O, O-H, C-H and C=O, were also detected, shown in Figure 7d; most of these organic functional groups were also detected in the EPS from the ZW123 bacterium (Figure 7b).…”
Section: Ftir Analysesmentioning
confidence: 74%
“…Mg/Ca ratios do not only affect the mineral phase but also the crystallinity. In the previous studies, with increasing Mg/Ca ratios, the crystallinity of monohydrocalcite induced by Staphylococcus epidermis Y2 decreased [29], whereas that induced by the halophile Halomonas smyrnensis WMS-3 increased [11]. Other factors that have been investigated include the presence of crystal seeds and the culture conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the peak at 284.3 eV is assigned to the C-C and C-H, originating from lipids or side chains of amino acid, and the peak at 288.97 eV can be due to the O-C=O from carboxylic acid, carboxylate, or ester [38]. The O 1s peak at 530.69 eV (Figure 6d) also indicates the presence of C=O and O-C=O from carboxylic acids, carboxylates, carbonyls and amides [26]. There was one peak at 132.78 eV (Figure 6e) and this peak could be attributed to phosphate groups [39].…”
Section: Characteristics Of Biomineralsmentioning
confidence: 96%
“…The liquid culture medium inoculated with YXY2 bacteria (OD 600 = 1.0) at a volume ratio of 1:100 was set as the experimental group, and that inoculated with the same volume ratio of sterilized distilled water was set as the control group. Ammonia test of YXY2 bacteria, the concentration of ammonium ion, CA activity, concentrations of carbonate and bicarbonate ions, the calculation of pH values based on the concentration of ammonium, bicarbonate and carbonate ions were all conducted according to published papers [26][27][28][29]. ALP activities were measured according to a previous study [30] and the concentrations of phosphate ions were also measured with the molybdenum blue method [31].…”
Section: Physiological and Biochemical Characteristics Of Yxy2 Bacteriamentioning
confidence: 99%